USING INSTAGRAM STORY TO ENHANCE THE NARRATIVE TEXT WRITING SKILL OF THE TENTH GRADERS OF SMA NEGERI 1 MAGELANG IN THE SCHOOL YEAR 2017/2018 - agustina lestari wilujeng (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2018)
Writing is one of the English language skills that should be mastered by the students of senior high school. Some of the tenth graders of SMA Negeri 1 Magelang still get difficulties in writing English especially narrative text. There are two main objectives of this research. The first one is to know whether the use of Instagram Story can increase the learning motivation of writing narrative text and the second is to know how great the enhancement of the narrative text writing skill of the tenth graders of SMA Negeri 1 Magelang who are taught by using Instagram Story is. The writer conducted a classroom action research. To collect the data, the writer used test and non-test techniques. The data were analyzed by using quantitative and qualitative data analysis technique. The result of analysis of the data showed that the use of Instagram Story can increase the students’ learning motivation and enhance their writing skill in narrative text. Based on the results above, the writer concluded that Instagram Story can increase students’ learning motivation of writing Narrative text of the tenth graders of SMA Negeri 1 Magelang in the school year 2017/2018. There is also a great enhancement of the Narrative text writing skill of the tenth graders of SMA Negeri 1 Magelang in the school year 2017/2018 who are taught by using Instagram Story.